DEVELOPMENT OF CANVA-BASED MATHEMATICS LEARNING MEDIA ON NUMBER PATTERN MATERIAL - Leony Eriani Johanis; Bakher Nenotaek (FKIP Universitas Mataram, 2026)
This research is a research and development (R&D) project that aims to produce a Canva-based interactive learning media entitled